1878 Miss. Laws 27, 29, ch. 3, §§ 8, 12 - (:unkn) unknown (General Publisher, 1878)
Mandated tax assessors to have prepared lists of taxable items, including pistols, Bowie knives, dirks, and sword canes.
--
Keywords: TAX - PROPERTY OR SALES